INFLUENCE OF ELECTRICAL ENERGY QUALITY ON TECHNOLOGICAL PROCESSES IN PLANT GROWING - Synyavsky, A.; Savchenko, V. (Energy and Automation, 2016)
The results of research of influence electricity quality indicators deviation on technological processes in grain storage, greenhouse, vegetable and fruit store are shown. The technological losses in electricity quality indicators deviations from nominal value are established.